Evaluation Calculation of Flood Design with Hydrograph Method Nakayasu, Limantara and Snyder in Catchhement River Way Tebu - Yasril Yasril; Aprizal Aprizal; A Nurhasanah (Bandar Lampung University (UBL), 2017)
Synthetic unit hydrograph is a synthetic based hydrograph of watershed parameters. One way to find out the magnitude of the flood watershed of Way Tebu River Basin is to predict the amount of flow from existing rain data, Therefore rainfall data as the main input of rain diversion process becomes a very important thing and must have a high level of accuracy. The research presents a simple approach to determine peak discharge and unit hydrograph form in the Waytebu River Basin. Several methods of unit synthesis hydrograph such as Nakayasu, Limantara and Snyder are used to calculate peak discharge and hydrograph form. Flood discharge plans with various reworks in each method, providing mixed results. The greatest result is the Limantara HSS (Q25 = 1,413.13 m3 / sec) and the smallest HSS Snyder (Q25:814,57 m3 / s), while HSS Nakayasu (Q25 = 922.93 m3 / s). From the hydrograph comparative analysis of the three methods for Limantara method, the top time is happened at (Tp: 5.57) with top flow (Qp: 10,19 m3 / s), While Nakayasu method has the same top time at (Tp: 5,93 ) with top flow (Qp: 11.65 m3 / s) and Snyder method top time happened ad (Tc: 5.57) with top flow (Qp: 10.19 m3 / s)